Impact of Receiving Secondary Results from Genomic Research: A 12‐Month Longitudinal Study. Issue 3 (22nd November 2017) - Wynn, Julia; Martinez, Josue; Bulafka, Jessica; Duong, Jimmy; Zhang, Yuan; Chiuzan, Codruta; Preti, Jain; Cremona, Maria L.; Jobanputra, Vaidehi; Fyer, Abby J.; Klitzman, Robert L.; Appelbaum, Paul S.; et al.
Abstract: The impact of returning secondary results from exome sequencing (ES) on patients/participants is important to understand as ES is increasingly utilized in clinical care and research. Participants were recruited from studies using ES and were separated into two arms: 107 who had ES and were offered the choice to learn secondary results (ES group) and 85 who had not yet had ES (No ES group). Questionnaires were administered at baseline and 1 and 12 months, following results disclosure (ES group) or enrollment (No ES group). While the majority (65%) elected to learn all results following pre‐test counseling, it was reduced from the 76% who indicated a desire for all results at baseline. Thirty‐seven percent received results associated with an increased personal disease risk. There were no differences in changes in any of the psychological and social measures from baseline to post‐results disclosure between the ES and No ES groups. Receiving a wide range of secondary findings appeared to have little measurable impact on most participants. The experience of learning secondary results may be related to participants' previous experiences with genetics, as well as the genetic counseling provided. Future research with a more diverse, genetically naïve group, as well as scalable methods of delivery, is needed.